Early Childhood Education to Promote Health Equity: A Community Guide Systematic Review. Issue 5 (September 2016) - Hahn, Robert A.; Barnett, W. Steven; Knopf, John A.; Truman, Benedict I.; Johnson, Robert L.; Fielding, Jonathan E.; Muntaner, Carles; Jones, Camara Phyllis; Fullilove, Mindy T.; Hunt, Pete C.
Abstract : Context: Children in low-income and racial and ethnic minority families often experience delays in development by 3 years of age and may benefit from center-based early childhood education. Design: A meta-analysis on the effects of early childhood education by Kay and Pennucci best met Community Guide criteria and forms the basis of this review. Results: There were increases in intervention compared with control children in standardized test scores (median = 0.29 SD) and high school graduation (median = 0.20 SD) and decreases in grade retention (median = 0.23 SD) and special education assignment (median = 0.28 SD). There were decreases in crime (median = 0.23 SD) and teen births (median = 0.46 SD) and increases in emotional self-regulation (median = 0.21 SD) and emotional development (median = 0.04 SD). All effects were favorable, but not all were statistically significant. Effects were also long-lasting. Conclusions: Because many programs are designed to increase enrollment for high-risk students and communities, they are likely to advance health equity. Abstract : This review investigates the potential of center-based early childhood education to foster the larger public health goal of health equity, with a focus on low-income and racial and ethnic minority populations in the United States.